Runaway Inflation in Chile, 1970-1973 - Edwards, Sebastián (Estudios de Economía, 2025)
In this essay, I argue that the explosion of inflation during the Salvador Allendeadministration in Chile (above 1,500% on a six-month annualized measure)was predictable. The government’s use of massive and strict price controlsgenerated acute macroeconomic imbalances. I postulate that the combinationof runaway inflation, shortages, and black markets generated major hostilityamong the middle class and that that unhappiness reduced the support for theUnidad Popular government.